Perceptual grouping, motion discrimination, and shape completion of four-sided figures in younger and older adults - Cali, Jessica N. (My University, 2019)
The present dissertation investigates perceptual grouping and shape completion in motion in younger and older observers. The first set of experimental results, Chapter 2, provides a set of exploratory experiments which characterize the nature of a motion grouping task, uncovering accurate direction discrimination when the stimulus contains a cue for global grouping, but compelling illusory motion when the stimulus does not contain that cue. Chapter 3 builds on the findings of Chapter 2 by measuring biases in motion integration that lead to the illusory motion. Chapter 3 extends this paradigm into older adult observers, and explores various stimulus variants and tasks to add to the characterization of this effect. In Chapter 4 the concepts of grouping and motion perception are examined in the context of shape completion by measuring the accuracy of aspect ratio, size, and area discrimination in younger and older adults. Chapter 4 concludes that older adults are worse at discriminating characteristics of shapes, but are similarly affected by incomplete or occluded stimuli as younger adults. On the whole, the dissertation demonstrates several novel findings in the perceptual organization literature, and investigates many of these phenomena into older adults populations. Throughout the dissertation, a central theme concerns the concept of behavioural measurement of perceptual processes, and consequently many of the phenomena are studied using several types of measurements and tasks to ensure a complete picture of the perceptual experience. The current dissertation presents a novel and important addition to the current literature in perceptual grouping and shape completion.
Perceptual grouping of shape in motion
Keywords: perception; vision; aging; motion; shape